INFLUENCE OF HEAT TREATMENT AND MODIFIED ATMOSPHERES PACKAGING ON THE CHEMICAL COMPOSITION OF DATE DEGLET NOUR DURING STORAGE IN COLD (Sciences & Technologie. C, Biotechnologies, 2007)
A compared study of the simple and combined action ofprocessing and storage has been carried on the date variety Deglet Nour. The samples were heat treated and/or packed in polyethylene film for modified atmospheres then stored in cold (10°C) and ambiant temperature (22°C) for 05 months. Results showed that the content in water is similar to the content of water in the half-soft date varieties. Either packed or unpacked refrigerated shares preserve their moisture, while shares stored at room temperature have dried. In control samples, a progressive diminution of the pH values has been observed during the storage. On the other hand, cold and heat treatment stabilizes the pH and the acidity. The content in total sugars decreases strongly during the storage, particularly at ambiant temperature. The cold slows considerablythis trend and a greater stability is recorded in heat treated - packed shares. The content in reducing sugars is more stable in shares heat treated- chilled or heat treated -packed comparatively to the controls that present fluctuations. These variations are confirmed by the evolution of the saccharose rate inversion. The positive effect of the heat treatment appears clearly when it is associated with the cold and packaging. The phenolic compounds decrease with storage particularly for heat treated samples, while the weakest contents are noted in packed shares. In conclusion, the combined heat treatment - cold - modified atmospheres seems to insure the best behavior of the date that preserves perfectly its initial characteristics of fresh fruit and an excellent market quality.